2015
DOI: 10.5897/ajest2014.1780
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the concentrations of lead, cadmium and zinc in surficial sediments from two shallow tectonic freshwater lake basins, kenya

Abstract: Sources of metals in the environment are widespread and data on typical concentrations in the various media and environmental settings exits worldwide. Distribution and comparative concentrations of some selected metals in surface sediments of two shallow tectonic freshwater basins were assessed, as useful indicators of the level or magnitude of anthropogenic influences, as well as other aquatic processes, considering the increasing challenges in management of waste disposal. Concentrations of Pb, Cd and Zn in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…TDS vales ranged from 300-305mg/l with a mean value of 302.63±2.00 mg/l during dry season while in the wet season, the values ranged from 183-433mg/l with a mean value of 297.5±113.11 mg/l.The results indicates that the TDS values were higher in dry season than wet season. A previous study in Lake Baringo revealed similar results of high TDS (Mwamburi, 2015;Kumar et al,2015).However,(Islam and Azam, 2015;Manohara et al, 2019) in their studies observed high TDS values during the wet seasons resulting from run-off in wet seasons. TDS values were within the acceptable National Environmental Management Authority (NEMA, Kenya) limits of 1200 mg/l for natural water.…”
Section: Resultsmentioning
confidence: 73%
“…TDS vales ranged from 300-305mg/l with a mean value of 302.63±2.00 mg/l during dry season while in the wet season, the values ranged from 183-433mg/l with a mean value of 297.5±113.11 mg/l.The results indicates that the TDS values were higher in dry season than wet season. A previous study in Lake Baringo revealed similar results of high TDS (Mwamburi, 2015;Kumar et al,2015).However,(Islam and Azam, 2015;Manohara et al, 2019) in their studies observed high TDS values during the wet seasons resulting from run-off in wet seasons. TDS values were within the acceptable National Environmental Management Authority (NEMA, Kenya) limits of 1200 mg/l for natural water.…”
Section: Resultsmentioning
confidence: 73%